A study on public transport quality of service from user of view (casestudy: Kota Kinabalu) - Muhammad Ismail, Jaafar (2014)
On 9 july 2009 the government introduces the" Government Transformation Plan" (GTP), which one of the agenda from six of "National Key Result Area" (NKRA) is to improve urban public transportation system in Malaysia. The common transportation system in Malaysia is now at level not satisfactory because almost every day all media will talk about how bad transportation system now days in Malaysia. the good transportation system should have a punctual schedule system, offering affordable fares, provide comfort to the user, less waiting time and also provide safe journey to the passage that board the bus. This all kind of features should be providing to the transportation system in order to attract people to use public transport. This study about point of view bus service in kota kinabalu. This study will produce a consumer perception of bus transport services. This study also aimed to get feedback on the user perception towards services and user satisfaction about the features on the bus services. In addition, the survey was also to identify improvement the need to be added and forwarded from the aspect of existing services and facilities. 43% use city bus every day, while 42% use this on weekends only. On the result its shows Interm of comfort, the user indicates that the three aspects that need to be repaired is clean city is a major problem with the eye -163 bus, bus curtain (-66), air conditioning (-92) and the best services and friendlines of staff with the average of 1 77.Interm of convinience result, respondent said the fares is affordable ,while 24% say it was expensive. Next result is waiting time, 57% 75% respondent said there waiting the bus about 5- 10minute,second is 20% waiting about 10-15minute,17% waiting for 15-20 minute. Since the bus is not cleannes, so city bus need to improve of their cleannes of bus and replace to new curtain and service of bus aircond.